Implementation of Problem Based Learning Learning Models in Improving Learning Outcomes - La Amaludin (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2023)
The low learning outcomes at Madrasah Ibtidaiyah Waiselang are one of the results of unattractive learning methods. This is caused by the lack of student involvement in the learning process in class, due to the dominant role of educators in the learning process. Apart from these factors, educators still use conventional learning models, so that the achievement of student learning outcomes is low. To overcome this problem, it is necessary to apply a problem-based learning that is oriented towards solving concrete problems so that student learning outcomes increase. The study used descriptive analysis to determine students' cognitive, affective and psychomotor learning outcomes. In the pre-cycle there were no students who passed with an average student score of 65 in the sufficient category. In cycle I, student completeness reached 80.95% and the average student score was at a very good level. Meanwhile, in cycle II, student learning completeness increased significantly to 85.71% with an average student score at a very good level. With a classical completeness score of 85.71%, 85% of classical learning completeness is fulfilled so that the research is not continued in the next cycle. The application of Problem based learning can improve student learning outcomes.